One new genus and species of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China - Pan, Yangyang; Bian, Xun (Zootaxa, 2024)
One new genus with one new species is proposed in this paper according to the newly obtained specimen from Yunnan deposited in Guangxi Normal University. To better distinguish the new genus, the morphological illustrations of twelve known belonging to five allied genera were provided.